Refiguring resurrection : a biblical and systematic eschatology - Harris, Steven Edward (Baylor University Press; Waco, Texas, 2023)
"Develops a systematic account of the doctrine of resurrection from Scripture, Christian tradition, and contemporary theology"--
Keywords: Christian Bible Exegesis & Hermeneutics; Christian Systematic Theology; Christian Eschatology